Strategi Guru Pendidikan Agama Islam Dalam Pembentukan Kedisiplinan Siswa Di SMA Negeri 1 Jombang - Mustain Hamdy; Ahmad Shofiyul Himami; Abd. Rozaq (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
PAI teacher strategy is needed in the formation of student discipline character. Strategy is a pattern that is planned and determined intentionally to carry out activities or actions. The strategy includes the objectives of the activity, who is involved in the activities, the process of activities, and the means of supporting activities. The focus of this research includes: 1. How is the strategy of PAI teachers in the formation of discipline. 2. What are the inhibiting and supporting factors in the formation of discipline. The research objectives are: 1. To describe the strategy of PAI teachers in forming student discipline in SMA Negeri 1 Jombang. 2. Describing student discipline at SMA Negeri 1 Jombang. 3. Describe the factors supporting and inhibiting the formation of student discipline in SMA Negeri 1 Jombang? This study uses a qualitative method with a qualitative descriptive design that uses data collection techniques through observation, interviews and documentation. The results of the study show that: 1. The strategy used by PAI teachers in forming student discipline uses strategies inside and outside the classroom. The strategies in the classroom are using Expository, Inquiry and Reflective learning strategies and strategies outside the classroom are using exemplary methods, habituation and punishment. 2. The discipline applied at SMA Negeri 1 Jombang is time discipline, discipline to enforce and obey the rules, discipline in attitude and discipline in worship. 3. Supporting factors are the cooperation between the principal and the waka student, PAI teachers, teachers of other subjects, and a supportive family environment. While the inhibiting factor is the lack of awareness of the students themselves, many parents pay less attention to their children, especially in terms of discipline and its influence on the family and community environment.